2020
DOI: 10.1177/1352458520958360
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain network function during attention-modulated visual processing in multiple sclerosis

Abstract: Background: Multiple sclerosis may damage cognitive performance in several domains, including attention. Although attention network deficits were described during rest, studies that investigate their function during task performance are scarce. Objective: To investigate connectivity within and between task-related networks in multiple sclerosis during a visual attention task as a function of cognitive performance. Methods: A total of 23 relapsing-remitting multiple sclerosis (RRMS) patients and 29 healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Regionally, decreased FC in the dorsal attention and visual networks was shown in RRMS patients during a visual attention task ( 76 ). On the other hand, increased FC in the frontoparietal network, a hub-rich network, with the rest of the brain (both peripheral and nonhub regions) correlated with worse attention in an MS population including RR and progressive forms ( 68 ).…”
Section: Connectivity Substrates Of CI In Msmentioning
confidence: 99%
“…Regionally, decreased FC in the dorsal attention and visual networks was shown in RRMS patients during a visual attention task ( 76 ). On the other hand, increased FC in the frontoparietal network, a hub-rich network, with the rest of the brain (both peripheral and nonhub regions) correlated with worse attention in an MS population including RR and progressive forms ( 68 ).…”
Section: Connectivity Substrates Of CI In Msmentioning
confidence: 99%
“…The right intraparietal sulcus exhibits diminished activation in response to attention and working memory tasks in multiple sclerosis according to a recent meta-analysis (Kollndorfer et al 2013). In our previous study we also showed that functional connectivity over and above task-related synchronization decreases between the right intraparietal sulcus and the right frontal eye field, another important region in the dorsal attention network, during a visual attention task (Veréb et al 2020). These results are corroborated by earlier accounts of a shift of perceptual bias in multiple sclerosis patients, which, based on our findings, might be caused by a disruption of interhemispheric balance in the attention system (Gilad et al 2006).…”
Section: Discussionmentioning
confidence: 84%
“…Currently, the only option for monitoring their therapeutic efficacy in everyday practice is clinical (i.e., the presence or absence of relapses or the presence or lack of EDSS progression in progressive disease forms) and/or MRI measures (i.e., new or equivocally enlarging lesions, number of black holes, contrast enhancement and, if available, total brain/grey matter atrophy). The problem with these methods in conventional MS care is their inability to forecast disease activity, and they might not capture subclinical processes [ 185 ], e.g., the development of psychopathological symptoms [ 459 ], cognitive dysfunction [ 460 , 461 , 462 ], attention network deficits [ 463 ] and subtle neurodegeneration. The soluble biomarkers found in the CSF and/or blood included in this review may eliminate this problem.…”
Section: Discussionmentioning
confidence: 99%